Alfabetização: estudo de desempenho em leitura e escrita de alunos do 2º, 3º, 4 e 5º anos do Ensino Fundamental - Silva, Simone Simões da (2024)
In 2023 many Brazilians still face problems with illiteracy among children, young people, and adults. The result of the 2016 National Literacy Assessment (ANA) showed that around 54% of students are at the lowest levels in Reading and Mathematics. The 2019 Brazilian Institute of Geography and Statistics (IBGE) survey recorded population illiteracy rates, demonstrating that 6.6% of the population aged 15 to 59 and 18% of people aged 60 and over do not know how to read. Adding to these rates, in the period 2020-2021, schools served students remotely, due to the Covid-19 health crisis. Mastery of written language is a fundamental prerequisite for a variety of learning and achievements, in addition to changing the way the brain interprets the world. This research aimed to verify the performance of students in the 2nd, 3rd, 4th, and 5th years of Elementary School at a municipal school in the city of São Paulo in reading, writing, and understanding text. Mastery of the alphabetic system was expected at the end of the 2nd year and progression of these skills until the 5th year. It also wondered if there was a balance or gap, during these years of school, between reading, writing, and understanding. Five activities built and adapted from the Instrument for Brief Assessment of Reading, Writing and Comprehension (IBALEC) designed to evaluate students from the 1st to 5th year of Elementary School were applied. The results demonstrated that there was no continuous progression in learning to read, write and understand text, and that most research participants still decode to read, which suggests that the necessary skills in literacy did not develop as expected by the National Common Curricular Base (BNCC – 2018). It is expected that the results can collaborate with educators and policies to improve current literacy rates